Considerations on biologicals for patients with allergic disease in times of the COVID‐19 pandemic: An EAACI statement. Issue 11 (6th November 2020) - Vultaggio, Alessandra; Agache, Ioana; Akdis, Cezmi A.; Akdis, Mubeccel; Bavbek, Sevim; Bossios, Apostolos; Bousquet, Jean; Boyman, Onur; Chaker, Adam M.; Chan, Susan; Chatzipetrou, Alexia; Feleszko, Wojciech; et al.
Abstract: The outbreak of the SARS‐CoV‐2‐induced coronavirus disease 2019 (COVID‐19) pandemic re‐shaped doctor‐patient interaction and challenged capacities of healthcare systems. It created many issues around the optimal and safest way to treat complex patients with severe allergic disease. A significant number of the patients are on treatment with biologicals, and clinicians face the challenge to provide optimal care during the pandemic. Uncertainty of the potential risks for these patients is related to the fact that the exact sequence of immunological events during SARS‐CoV‐2 is not known. Severe COVID‐19 patients may experience a "cytokine storm" and associated organ damage characterized by an exaggerated release of pro‐inflammatory type 1 and type 3 cytokines. These inflammatory responses are potentially counteracted by anti‐inflammatory cytokines and type 2 responses. This expert‐based EAACI statement aims to provide guidance on the application of biologicals targeting type 2 inflammation in patients with allergic disease. Currently, there is very little evidence for an enhanced risk of patients with allergic diseases to develop severe COVID‐19. Studies focusing on severe allergic phenotypes are lacking. At present, noninfected patients on biologicals for the treatment of asthma, atopic dermatitis, chronic rhinosinusitis with nasal polyps, or chronic spontaneous urticaria should continue their biologicals targeting type 2 inflammation via self‐application. In case of an active SARS‐CoV‐2 infection, biological treatment needs to be stopped until clinical recovery and SARS‐CoV‐2 negativity is established and treatment with biologicals should be re‐initiated. Maintenance of add‐on therapy and a constant assessment of disease control, apart from acute management, are demanded.